Pachyrhizus ahipa roots and starches: Composition and functional properties related to their food uses. Issue 5 (27th December 2013) - Doporto, María C.; Dini, Cecilia; Viña, Sonia Z.; García, María A.
<x xml:space="preserve">Abstract</x> Chemical composition of two accessions (N° 11 and Local) of Pachyrhizus ahipa was evaluated and their starches were characterized from a technological and nutritional point of view. Ahipa roots were characterized by their high protein (8–9%) level compared to other roots and tubers. Accession 11 exhibited higher starch content than Local accession. Compared to cassava, ahipa starch showed lower gelatinization temperature, exhibiting accession 11 the lowest value. Ahipa starch digestibility was similar to that of other leguminous plants. Accession 11 showed higher rapidly digestible (RD), resistant (RS) and lower slowly digestible (SD) starch than cassava. Rotational rheological assays indicated that gelatinized ahipa starch suspensions present a pseudoplastic thixotropic behavior and under dynamic assays they behaved as a weak gel. Finally, ahipa can be considered a very good source of starch and might be used as a functional food, contributing to increase the RD and SD fractions.